1990
DOI: 10.1682/jrrd.1990.04.0107
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses to arm ergometry and functional neuromuscular stimulation

Abstract: The hips and lower extremities of four complete paraplegic male subjects (T-6, T-7, T-8, and T-11) were stimulated with functional neuromuscular stimulation (FNS) via transcutaneous intramuscular electrodes (20 mA, 0-150 pulse width, and 20 Hz) . Cardiopulmonary (CP) and/or cardiovascular (CV) responses were measured during maximal (seated) arm ergometry (AE), FNS, and FNS + AE . Subjects' lower extremities were stimulated with a 2 s walking cycle via a microprocessor computer. Data were collected with a Senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Further empirical evidence from crossover studies supported the viewpoint that combined upper body voluntary exercise and FES-evoked leg exercise produced enhanced metabolic responses, which included higher peak VO 2 56,109-111 ; increased posttraining measurements of HR, VO 2 , VE, and Q 67, 99,112 ; larger SV; greater arteriovenous oxygen extraction 98 ; and increased peak power output. 42 The level of whole-body metabolism (METS) during FES alone was less than 50% of that observed during arm plus leg exercise, 113 and blood-borne lactic acid was also highest during hybrid exercise likely due to the larger muscle mass involved in such exercise. 113 In a self-controlled randomized trial of SCI individuals who performed FES-assisted rowing, Laskin and co-workers 114 observed that arm plus leg rowing evoked sig-nificantly higher VO 2 compared to FES leg stimulation only or voluntary manual rowing only.…”
Section: Metabolic Responses and Aerobic Fitnessmentioning
confidence: 99%
“…Further empirical evidence from crossover studies supported the viewpoint that combined upper body voluntary exercise and FES-evoked leg exercise produced enhanced metabolic responses, which included higher peak VO 2 56,109-111 ; increased posttraining measurements of HR, VO 2 , VE, and Q 67, 99,112 ; larger SV; greater arteriovenous oxygen extraction 98 ; and increased peak power output. 42 The level of whole-body metabolism (METS) during FES alone was less than 50% of that observed during arm plus leg exercise, 113 and blood-borne lactic acid was also highest during hybrid exercise likely due to the larger muscle mass involved in such exercise. 113 In a self-controlled randomized trial of SCI individuals who performed FES-assisted rowing, Laskin and co-workers 114 observed that arm plus leg rowing evoked sig-nificantly higher VO 2 compared to FES leg stimulation only or voluntary manual rowing only.…”
Section: Metabolic Responses and Aerobic Fitnessmentioning
confidence: 99%
“…Functional electrical stimulation (FES) has been used therapeutically to improve the health and independence of persons with paraplegia by activating and coordinating paralyzed lower-limb muscles, improving cardiovascular fitness [5], and decreasing the risk of diabetes [6], as well as reducing osteoporosis [7] * without adverse effects on the insensate joints [8]. Preliminary studies suggest that FES exercise and weight bearing also reduce the risk of pressure sores by improving tissue oxygen levels, increasing muscle bulk, and altering seated pressure distribution [9].…”
Section: Introductionmentioning
confidence: 99%
“…Referring to FES treadmill tetraplegic gait, there is a definite increase in oxygen consumption thus improving cardiovascular function (Fig. A) . For FES‐based paraplegic gait, oxygen consumption increases at the beginning, reaches a steady state, and decreases toward values of the beginning of gait within a short interval after end of gait.…”
Section: Functional Diagnoses and Therapymentioning
confidence: 99%